(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Question: What is the diversity and taxonomic structure of macrofungi in the Guba region of Azerbaijan? How many macrofungi are threatened? Locations: Guba District, Azerbaijan. Methods: field surveys, micromorphology studies follow Lodge et al. 2004 using a microscope Axio Imager Vert. A1 Carl Zeiss, Germany; identification of species follow Arora 1986, Grunert & Grunert, 2002, Horac 2005. Nomenclature: index fungorum www.indexfungorum.org, MycoBank www.mycobank.org, World Flora Online www.worldfloraonline.org Results: The article represents study on the diversity of forest ecosystems of Guba district based on the mushroom specimens collected in 2017–2022. Altogether 144 specimen including those kept at the mycological herbarium were involved to the study. The purpose of this work is to determine the species diversity, taxonomical composition and assignment to ecological groups of basidiomycetes of Guba district, taking into account modern taxonomical and nomenclatural novelties. As a result of study, 91 taxa (90 species and one intraspecific taxon) belonging to the 63 genera, 35 families and seven orders (Agaricales, Boletales, Cantharellales, Geastrales, Hymenochaetales, Russulales, Polyporales) were registered. Coprinellus domesticus and Russula flavisiccans represents new records for Azerbaijan. The ecological groups of fungi have been studied, species were irrespectively assigned to the saprobionts, symbionts, xylotrophes and parasites. The ecological role of Cuphophyllus pratensis and Gliophorus psittacinusis unclear, since they are found in moss, and it has been suggested that they can form a symbiosis. The distribution of these species depending on the altitude was also studied; fungal species were mainly noted in the low-mountain zone (51) and relatively less in the middle mountain zone (37). Three species (Bolbitius titubans, Mycena pura, Hymenopellis radicata) were recorded in both zones. Some of them grow along mountain slopes (Macrolepiota procera, Parasola plicatilis) and also occur in meadows. Rare and threatened mushroom species were identified based on IUCN Red List categories. Conclusions: The study of the macrofungal diversity of the Guba distric expands our knowledge of the fungi of the studied territory, and also creates an opportunity to compare the most mushroom-rich areas of the Greater Caucasus within Azerbaijan in order to document and identify the diversity of fungal species and propose measures for their effective use in future.